Assessment of developmental dysplasia of the hip using ultrasonography in infants - Hossain, Mohammad Mahbub; Monowara, Mahmuda (International Journal of Research in Medical Sciences, 2026)
Background: Developmental dysplasia of the hip (DDH) represents a spectrum of anatomical abnormalities that may lead to long-term functional impairment if not diagnosed and treated early. Ultrasonography allows real-time visualization of cartilaginous hip structures and is the preferred imaging modality during early infancy. This study aimed to evaluate ultrasonographic findings of DDH in infants and analyze associated demographic characteristics, risk factors and Graf classification patterns. Methods: This cross-sectional study was conducted at the Department of Radiology and Imaging, Bangladesh Shishu Hospital and Institute, Dhaka, Bangladesh, from July 2024 to June 2025. Thirty infants aged six months or younger underwent bilateral hip ultrasonography using the standardized Graf technique. Demographic variables, perinatal risk factors and sonographic parameters were recorded systematically. Data were analyzed using SPSS version 25.0. Results: Female infants constituted 63.3% of the study population. Normal hips (Graf type I) were identified in 46.7% of infants, while 23.3% demonstrated physiologic immaturity (type IIa). Moderate to severe dysplasia (types IIb-IV) was observed in 26.7% of cases. Reduced α-angle, shallow acetabulum and increased β-angle were the most frequent abnormal findings. The proportion of normal hips increased with advancing age, indicating progressive acetabular maturation. Conclusions: Ultrasonography is an effective, reliable modality for early detection of DDH, particularly among high-risk infants. Early identification facilitates timely intervention and may reduce the burden of late-presenting disease.